Business Strategy in Mexican Beer Industry: A Case Applying Game Theory - Vargas-Hernández, José G; Cambroni-de-Anda, Armando Francisco (Journal of Asian Business Strategy, 2012)
In this paper the two major breweries in Mexico, Grupo Modelo and Cuauhtémoc Moctezuma Brewering Company (Cervecería Cuahtemoc-Moctezuma) are analyzed which already have long formed part of an oligopoly because these two companies account for more than 99% of beer market in this country. All this analysis is made from the perspective of game theory. The main objective is to analyze the effects of competition and advertising from one to another brewer from a standpoint of game theory. This analysis is based on one of the clearest examples that have existed for years in a matter of advertising and competition among soft drink companies Coca-Cola and Pepsi-Cola.